The respective weights of facial signs on the perception of age and a tired‐look among differently aged Korean men. Issue 5 (5th April 2021) - Flament, Frederic; Abric, Aurelie; Prunel, Anne; Cassier, Matthieu; Delaunay, Caroline
Abstract: Objectives: To determine the respective weights of certain facial signs on the assessment of the perceived age and a tired‐look on Korean men of different ages. Material and Methods: Photographs were taken of the faces of 101 Korean men (20‐80 years) under standardized conditions. These photographs allowed to define 16 signs, which were then graded by 15 experts/dermatologists, using standardized scales provided by a referential Skin Aging Atlas. These signs were dispatched into 5 clusters, namely Wrinkles/Texture, Ptosis/Sagging, Cheek pores, Pigmentation, and Vascular signs. A naïve panel of 200 Korean individuals (100 women, 100 men), of similar age range, were asked, when viewing full‐face photographs, to (a) attribute on a 0‐10 scale their perception of a tired‐look and (b) estimate the age of the subject. Results: The severity of all clusters increased with age, although at different rates. The Wrinkles/Texture or Ptosis/Sagging showed a rather regular progression, whereas Vascular presented the weakest changes. Although perceived and real ages were found highly correlated, almost 85% of the subjects were judged older by 1‐15 years. The signs/clusters were found significantly correlated with perceived age, highly for Wrinkles/Texture and Ptosis/Sagging, moderate for Pigmentation, and low for Vascular and Cheek pores. The weights in perceived ages of Wrinkles/Texture and Ptosis/Sagging represent 81% and Pigmentation at 19%. Facial tired‐look of Korean men was found significantly correlated with perceived age. Although Vascular and Cheek pores were found not impacting, Wrinkles/Texture, Ptosis/Sagging, and Pigmentation presented a clear influence. Conclusion: Within facial clusters, Wrinkles/Texture, Ptosis/Sagging, and Pigmentation are major factors in the assessment of perceived age in Korean men. The perception of an increased tired‐look is significantly associated with increased perceived age.